Das materielle Erbe des Steinkohlenbergbaus in Deutschland Eine Handreichung zur Dokumentation und Digitalisierung in kleinen Sammlungen - Siemer, Stefan (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2020)
The publication aims to establish minimum standards for small museum collections of Germany's coal mining heritage, including the acquisition and documentation of objects. It focuses on photographic techniques, database creation, and the presentation of objects online. The guide is rounded out with a list of financial assistance options for small museums and an extensive bibliography.